A method for repairing and regenerating waste lithium iron phosphate positive electrode material and lithium battery
By performing discharge treatment, heat treatment, oxidation treatment and carbon coating treatment on the positive electrode material of waste lithium iron phosphate batteries, the problems of environmental pollution, high cost and reduced performance in the recycling process in the prior art are solved, and high efficiency and environmental protection are achieved Lithium iron phosphate positive electrode material regenerates.
Patent Information
- Application Number
- CN202411723233.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
When recycling waste lithium iron phosphate positive electrode materials, the prior art requires the use of strong acids, strong alkalis or high temperature conditions, resulting in environmental pollution, increased costs and reduced material performance, and long process cycles and high energy consumption, which limits large-scale applications.
By discharging and dismantling the waste lithium iron phosphate battery, the lithium iron phosphate positive electrode sheet is separated, and heat treated under an inert atmosphere to obtain waste lithium iron phosphate positive electrode black powder. Then heat treatment was performed in an environment with an oxygen content of more than 60%, lithium iron phosphate red powder was oxidized, and the lithium source was supplemented according to the test results, and then carbon deposition coating and reduction was carried out in a reducing atmosphere to obtain the regenerated lithium iron phosphate positive electrode material.
It realizes efficient repair and regeneration of waste lithium iron phosphate positive electrode materials, reduces environmental pressure, reduces energy consumption and process cycles, improves the environmental protection and performance consistency of the material, and is suitable for large-scale applications.
Smart Images

Figure CN119218966B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waste power battery recycling, and in particular to a method for repairing and regenerating waste lithium iron phosphate positive electrode materials and a lithium iron phosphate battery prepared by the method. Background Art
[0002] With the rapid development of the electric vehicle market, the demand for power batteries is also growing. As the positive electrode material of power batteries with the largest installed capacity, lithium iron phosphate (LiFePO 4 ) has the advantages of good safety performance, fast charging speed and long service life.
[0003] Lithium iron phosphate positive electrode materials are widely used in power batteries due to their high safety, long life and environmental protection. However, with the use of power batteries, a large amount of waste lithium iron phosphate positive electrode materials will also be scrapped. How to effectively recycle and reuse these waste materials has become an important research topic. The solution of the prior art is mainly to disassemble the battery and then separate the positive electrode, negative electrode, diaphragm and other parts. The recovery of lithium iron phosphate positive electrode materials is to extract the valuable metal elements therein by acid leaching, alkali leaching or high-temperature pyrolysis, and then synthesize new lithium iron phosphate positive electrode materials. However, these methods often require the use of strong acid, strong alkali or high temperature conditions, which will produce more wastewater and waste gas, not only polluting the environment, but also increasing the cost of recycling. Secondly, these methods often destroy the structure of lithium iron phosphate positive electrode materials, affect their performance, and make it difficult to apply them to the field of power batteries. Thirdly, due to the different sources of recycled waste lithium batteries, there may also be defects in the poor consistency of the performance of the regenerated lithium iron phosphate positive electrode materials. In addition, these methods have a long process cycle, cumbersome process and high energy consumption, which also limits their large-scale application. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and firstly provide a method for repairing and regenerating waste lithium iron phosphate positive electrode materials.
[0005] The method for repairing and regenerating waste lithium iron phosphate positive electrode materials provided by the present invention comprises the following steps:
[0006] S1. Discharging and dismantling the waste lithium iron phosphate battery to separate the lithium iron phosphate positive electrode sheet, and then heat-treating the obtained positive electrode sheet under an inert atmosphere to separate the lithium iron phosphate positive electrode sheet from the current collector to obtain the waste lithium iron phosphate positive electrode black powder;
[0007] S2 heat-treating the waste lithium iron phosphate positive electrode black powder again in an environment furnace with an oxygen content higher than 60%, while removing impurities and oxidizing the surface of the lithium iron phosphate red powder to obtain oxidized lithium iron phosphate red powder;
[0008] S3: testing the P, Fe, and Li content of the lithium iron phosphate oxide red powder obtained in step S2, and appropriately supplementing the lithium source according to the test result, and then mixing the lithium iron phosphate oxide red powder with the lithium source by ball milling to obtain a lithium-supplemented lithium iron phosphate oxide mixture;
[0009] S4: placing the lithium-replenished oxidized lithium iron phosphate mixture in a reducing atmosphere furnace, passing an inert gas containing carbonizable small molecular organic matter, and after heat treatment, allowing the lithium-replenished oxidized lithium iron phosphate mixture to be carbon-deposited and reduced in the reducing atmosphere to obtain a regenerated lithium iron phosphate positive electrode material.
[0010] The method for repairing and regenerating waste lithium iron phosphate positive electrode materials provided by the present invention comprises the following steps: disassembling the waste lithium iron phosphate positive electrode materials after discharging treatment by immersion in a NaCl solution, removing impurities in an environment with an oxygen content higher than 60%, replenishing a lithium source according to the tested contents of P, Fe and Li elements in the oxidized lithium iron phosphate red powder, and heat-treating the waste lithium iron phosphate positive electrode materials with carbonizable small molecules by entraining an inert gas to achieve reduction and carbon coating. The various process steps cooperate with each other to complete the repair and regeneration of the waste lithium iron phosphate positive electrode materials, and obtain positive electrode materials that can be directly used to prepare lithium iron phosphate lithium batteries.
[0011] The present invention effectively solves the problem of recycling lithium iron phosphate positive electrode materials in power batteries, improves resource utilization, reduces the environmental pressure of lithium battery production, realizes direct regeneration of lithium iron phosphate positive electrode materials, avoids strong acid, strong alkali or high temperature conditions in traditional recycling methods, has a short process cycle, low energy consumption, does not generate any wastewater, reduces environmental pollution, improves the environmental friendliness of the recycling process, is conducive to large-scale application, is suitable for industrial production, and meets the current social demand for efficient and environmentally friendly recycling technology.
[0012] The present invention also provides a lithium iron phosphate battery prepared by using the above-mentioned repaired and regenerated waste lithium iron phosphate positive electrode material. Since the surface of the above-mentioned repaired and regenerated lithium iron phosphate particles is coated with carbonaceous materials, the conductivity and rate performance of the lithium iron phosphate battery can be effectively improved, and its lithium iron phosphate 0.1C gram capacity reaches more than 155mAh / g, and after 1000 cycles of charge and discharge, the capacity retention rate is not less than 90.0%. In this way, the recycling of lithium-ion battery materials is realized, while reducing the manufacturing cost of lithium batteries, the electrochemical properties of lithium batteries such as the first effect and high capacity are reliably guaranteed, and the recycling and application process of lithium batteries is promoted, which has broad market prospects and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a schematic diagram of the device for preparing carbonizable small molecule organic matter with inert gas according to the present invention. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0015] The method for repairing and regenerating waste lithium iron phosphate positive electrode materials provided by the present invention comprises the following steps:
[0016] S1 The waste lithium iron phosphate battery is discharged, crushed and disassembled to separate the lithium iron phosphate positive electrode sheet, and then the obtained positive electrode sheet is heat-treated under an inert atmosphere to separate the lithium iron phosphate positive electrode sheet from the current collector to obtain the waste lithium iron phosphate positive electrode black powder.
[0017] In this step, the recycled waste lithium iron phosphate batteries are first subjected to a discharge treatment. The discharge treatment method is to soak the waste lithium iron phosphate batteries in a 5wt% to 20wt% NaCl solution for 30 to 240 minutes. Based on the fact that sodium and lithium have the same external electronic arrangement and coordination environment, sodium can easily replace the lithium in the lithium iron phosphate, so that all active lithium ions inside the waste lithium iron phosphate batteries are embedded back in the lithium iron phosphate positive electrode material, avoiding waste of resources, reducing the amount of additional lithium source supplement in subsequent processes, and making the waste lithium iron phosphate batteries completely discharged to 0V, so that there will be no safety issues during the disassembly of the waste lithium batteries.
[0018] After the discharge is completed, the lithium iron phosphate positive electrode sheet, negative electrode sheet, diaphragm and shell are separated by physical methods such as mechanical crushing and disassembly, and then the obtained positive electrode sheet is heat-treated under an inert atmosphere at a temperature of 300-600°C and a heat treatment time of 30-180 minutes to separate the lithium iron phosphate positive electrode sheet from the current collector to obtain waste lithium iron phosphate positive electrode black powder.
[0019] Specifically, the inert atmosphere is one or more of nitrogen, argon, and helium.
[0020] S2 The waste lithium iron phosphate positive electrode black powder is heat-treated again in an environment furnace with an oxygen content higher than 60%, and the surface of the lithium iron phosphate red powder is oxidized while removing impurities to obtain oxidized lithium iron phosphate red powder.
[0021] In this step, the waste lithium iron phosphate positive electrode black powder is heat-treated again in an environment with an oxygen content higher than 60%, and the heat treatment temperature is 400°C to 800°C for 60 to 300 minutes. On the one hand, the inactive impurities in the waste lithium iron phosphate positive electrode black powder, such as binders, conductive agents, electrolyte residues, etc., can be completely removed to improve the purity of the final product. On the other hand, the surface of the waste lithium iron phosphate positive electrode black powder is oxidized, so that it can be more fully contacted with the supplemented lithium source in the subsequent process and prepare for the formation of a uniform carbon coating layer in the subsequent vapor deposition process.
[0022] S3: testing the P, Fe, and Li content of the lithium iron phosphate oxide red powder obtained in step S2, and appropriately supplementing the lithium source according to the test result, and then mixing the lithium iron phosphate oxide red powder with the lithium source by ball milling to obtain a lithium-supplemented lithium iron phosphate oxide mixture.
[0023] Since the recycled waste lithium batteries come from different sources, this step uses ICP to test the P, Fe, and Li element contents of the oxidized lithium iron phosphate red powder, and appropriately supplements the active lithium lost in the waste lithium iron phosphate batteries according to the test results, so that the electrochemical properties of the regenerated lithium iron phosphate positive electrode material are consistent. In this way, when using the recycled positive electrode material to prepare lithium batteries, the total capacity, energy density, and cycle life requirements of the lithium battery can be met to ensure the electrochemical performance of the prepared lithium battery.
[0024] The lithium source should be supplemented so that the molar ratio of P, Fe and Li in the lithium iron phosphate red powder satisfies the following relationship: P:Fe:Li=(1±0.01):(1±0.01):(1.05±0.005). The lithium source is one or more of lithium carbonate, lithium acetate, lithium hydroxide, lithium nitrate, lithium oxide, lithium phosphate, lithium chloride or lithium fluoride.
[0025] The oxidized lithium iron phosphate red powder and the lithium source are mixed and ball-milled at 400-1200 rpm for 6-15 hours to reduce the particle size of the oxidized lithium iron phosphate red powder and the lithium source mixture, and ensure that the oxidized lithium iron phosphate red powder and the lithium source can be mixed more evenly, and is conducive to the subsequent carbon coating on the surface of the lithium iron phosphate particles. The particle size after grinding meets the following requirements: D50≤2um, (D90-D10) / D50≤2.5.
[0026] S4: placing the lithium-replenished oxidized lithium iron phosphate mixture in a reducing atmosphere furnace, passing an inert gas containing carbonizable small molecular organic matter, and after heat treatment, allowing the lithium-replenished oxidized lithium iron phosphate mixture to be carbon-deposited and reduced in the reducing atmosphere to obtain a regenerated lithium iron phosphate positive electrode material.
[0027] This step is to carbon-deposit and reduce the lithium iron phosphate mixed material in a reducing atmosphere, and use organic gas containing a carbon source to heat and flow the gas, so that the organic molecules undergo pyrolysis and redox reactions at high temperatures, cracking and carbonizing, and hydrogen elements are converted into hydrogen, CH 4 →C+2H 2 , gaseous molecules gradually deposit into solid carbon, reducing the lithium-replenished oxidized lithium iron phosphate mixture, and carbon atoms gradually deposit on the surface of the oxidized lithium iron phosphate mixture to form carbon-coated lithium iron phosphate. In this way, in-situ reduction and coating are carried out simultaneously and a tight and uniform carbon coating layer can be obtained, which greatly improves the efficiency of the positive electrode material repair and regeneration, and also improves the electrochemical performance of the positive electrode material.
[0028] The specific preparation method of the inert gas with carbonizable small molecule organic matter is as follows: a device for carbonizing small molecule organic matter with inert gas is set outside the reducing atmosphere furnace (see Figure 1 ), the device comprises a container 1, and a liquid carbonizable small molecule organic matter (organic solution 4) is placed in the container 1, and sufficient space is reserved for the liquid in the container 1 so that the gas can fully contact and react with the organic solution 4. An air inlet pipe 2 and an air outlet pipe 3 are provided at the upper end of the container 1, wherein the air inlet pipe 2 is a long conduit, one end of which is fed with an inert gas, and the other end is inserted into the container 1, and the pipe mouth of the air inlet pipe 2 is placed near the bottom of the container 1, and the inert gas enters the bottom of the container 1 after coming out of the pipe mouth, and mixes with the liquid carbonizable small molecule organic matter. Since the inert gas enters from the bottom of the container 1, the inert gas and the liquid carbonizable small molecule organic matter have sufficient contact area and time, and can ensure that the carbonizable small molecule organic matter is attached to the inert gas, forming an air flow overflow carrying the carbonizable small molecule organic matter. One end of the gas outlet pipe 3 is connected to the inner cavity of the container 1, and the other end is connected to the inner cavity of the reducing atmosphere furnace. The gas flow carrying the carbonizable small molecule organic matter rises and enters the reducing atmosphere furnace through the gas outlet pipe 3, so that the lithium iron phosphate mixed material is reduced in the reducing atmosphere and forms a carbon deposition coating. It should be noted that the above-mentioned specific preparation method of the inert gas carrying the carbonizable small molecule organic matter is only an embodiment of the present application. As long as it can ensure that the carbonizable small molecule organic matter is attached to the inert gas, any method of forming a gas flow carrying the carbonizable small molecule organic matter and exporting it is within the protection scope of the present application.
[0029] In the above process, the amount of carbonizable small molecule organic matter participating in the subsequent reaction can be controlled by adjusting the flow rate of the inert gas. Depending on the type of organic matter, the amount of carbonizable small molecule organic matter in the mixed gas after passing through container 1 accounts for approximately 0.02%~0.5%, that is, the amount of carbonizable small molecule organic matter participating in the subsequent reaction is approximately 0.02%~0.5% of the inert gas flow rate.
[0030] The inert gas is one or more of nitrogen, argon, and helium, and the carbonizable small molecule organic matter is at least one of methanol, ethanol, acetone, formic acid, acetic acid, ethyl acetate, and ether. The cracking and carbonization temperatures of these compounds match the synthesis temperature of lithium iron phosphate, and they are low in cost, easy to volatilize, and easy to attach to the inert gas to form a mixed gas flow.
[0031] The inert gas with carbonizable small molecular organic matter is heat treated in a reducing atmosphere furnace at a temperature of 600-900°C and a holding time of 6-18 hours. Within this temperature range, on the one hand, the carbonization of organic molecules can be achieved to achieve carbon coating, and on the other hand, the reaction temperature of the mixed material is converted into lithium iron phosphate. Within this time range, the reduction of the lithium-supplemented oxidized lithium iron phosphate mixed material and the formation of carbon-coated lithium iron phosphate can be guaranteed.
[0032] In the above method of the present application, the lithium element in the lithium iron phosphate positive electrode material is recovered after disassembly after immersion in NaCl solution for discharge treatment; impurities are removed in an environment with an oxygen content higher than 60%, which improves the quality of the positive electrode material and oxidizes the surface of the waste lithium iron phosphate positive electrode black powder, which is conducive to the subsequent carbon deposition coating reduction; the lithium source is supplemented according to the P, Fe, and Li element contents of the tested oxidized lithium iron phosphate red powder, which solves the defect of inconsistent supply of recycled waste lithium iron phosphate batteries and ensures the consistency of the electrochemical performance of the regenerated lithium iron phosphate positive electrode material; inert gas is used to carry carbonizable small molecule organic matter for heat treatment to achieve reduction and carbon coating, which improves the repair and regeneration efficiency of the positive electrode material while also improving its electrochemical performance. The above process steps cooperate with each other to complete the repair and regeneration of waste lithium iron phosphate positive electrode materials and obtain positive electrode materials that can be directly used to prepare lithium iron phosphate lithium batteries.
[0033] The repaired and regenerated lithium iron phosphate positive electrode material of the present invention is made into a lithium iron phosphate battery (button half-cell), and a charge and discharge test is carried out within a cut-off voltage range of 2.0 to 3.75 V. The reversible capacity is above 155 mAh / g, and after 1000 charge and discharge cycles, the capacity retention rate is higher than 90%, which effectively guarantees the electrochemical performance of the lithium ion battery while reducing the manufacturing cost of the lithium ion battery.
[0034] The method for repairing and regenerating the above-mentioned waste lithium iron phosphate positive electrode material is further described in detail below in conjunction with specific embodiments.
[0035] Embodiment 1:
[0036] S1 soaks the waste lithium iron phosphate battery in a 10% NaCl solution for 120 minutes, performs discharge treatment, and then disassembles and separates the positive electrode sheet; then places the obtained positive electrode sheet in N 2 The waste lithium iron phosphate positive electrode black powder was obtained by sintering at 500°C in an atmosphere furnace for 120 minutes to separate the positive electrode sheet from the current collector.
[0037] S2: The positive electrode black powder obtained in step S1 is transferred to an oxygen-containing atmosphere furnace, and a gas with an oxygen content of 60% is passed through it. After a heat treatment at 500° C. for 60 minutes, lithium iron phosphate red powder is obtained.
[0038] S3 The lithium iron phosphate red powder obtained in step S2 was subjected to ICP test, and the molar ratio of Li, Fe, and P was 0.951:1.004:1.002. A planetary ball mill was used for dry grinding, and lithium iron phosphate red powder and lithium hydroxide were added to the ball mill to make the molar ratio of Li, Fe, and P of the lithium iron phosphate mixture replenished with lithium oxide to be 1.052:1.001:1.003. The ball milling speed was 600rpm, and the lithium iron phosphate mixture replenished with lithium oxide was obtained after 9 hours. Laser particle size test showed that the lithium iron phosphate mixture replenished with lithium oxide had D10=0.76um, D50=1.82um, and D90=5.13um.
[0039] S4: placing the ground lithium-supplemented oxidized lithium iron phosphate mixture in an inert atmosphere furnace, and simultaneously introducing a nitrogen gas flow through an inlet pipe 2 into a nitrogen gas-carrying small molecular organic carbonization container 1 outside the inert atmosphere furnace (see Figure 1 ), container 1 is filled with methanol solution (organic solution 4), nitrogen is allowed to enter the bottom of the inner cavity of container 1 from the inlet pipe 2, and after contacting with the methanol solution, the nitrogen gas flow with methanol is used as a protective atmosphere to enter the inert atmosphere furnace from the outlet pipe 3, and the methanol content in the mixed gas is about 0.3% of the nitrogen gas flow. The temperature in the furnace is raised to 750°C and kept warm for 12 hours, so that the lithium iron phosphate mixed material of lithium supplementation oxidation is reduced in the reducing atmosphere and forms a carbon deposition coating. After natural cooling, the regenerated lithium iron phosphate positive electrode material is obtained.
[0040] The above-mentioned regenerated lithium iron phosphate positive electrode material was made into a 2035 button-type lithium battery, and charge and discharge tests were carried out in the cut-off voltage range of 2.0 to 3.75V. The first reversible capacity and the capacity retention rate after 1000T cycles were recorded. The results showed that the reversible capacity was 157.2mAh / g and the cycle performance was 94.5%, which fully met the requirements of commercial lithium iron phosphate batteries.
[0041] Comparative Example 1:
[0042] Steps S1 and S2 are the same as those in Example 1.
[0043] S3: The lithium iron phosphate red powder obtained in step S2 is subjected to ICP testing, wherein the molar ratio of Li, Fe and P is 0.951:1.004:1.002.
[0044] A planetary ball mill was used for dry grinding. The lithium iron phosphate red powder in step S2 was added to the ball mill. The ball milling speed was 300 rpm. After 9 hours, an oxidized lithium iron phosphate mixture was obtained. Laser particle size test showed that the particle size of the oxidized lithium iron phosphate mixture was D10 = 0.96 um, D50 = 3.23 um, and D90 = 13.45 um.
[0045] Step S4 is the same as that in Example 1.
[0046] The lithium iron phosphate positive electrode material obtained in this comparative example 1 was made into a 2035 button-type lithium battery, and a charge and discharge test was carried out in the cut-off voltage range of 2.0 to 3.75 V. The first reversible capacity and the capacity retention rate after 1000T cycles were recorded. The results were: the reversible capacity was 152.4 mAh / g, and the cycle performance was 56.6%.
[0047] By comparison, it can be seen that in Comparative Example 1, no lithium source supplement was performed on the lithium iron phosphate red powder, the ball milling speed was lower than the range set in this application, and the particle size after grinding was also higher than the range set in this application. Although the reversible capacity was slightly lower than that in Example 1, the cycle performance was about 38 percentage points lower than that in Example 1.
[0048] Embodiment 2:
[0049] S1 soaks the waste lithium iron phosphate battery in a 15% NaCl solution for 150 minutes, performs discharge treatment, and then disassembles and separates the positive electrode sheet; then places the obtained positive electrode sheet in N 2 The waste lithium iron phosphate positive electrode black powder was obtained by sintering at 600°C in an atmosphere furnace for 120 minutes to separate the positive electrode sheet from the current collector.
[0050] S2: The positive electrode black powder obtained in step S1 is transferred to an oxygen-containing atmosphere furnace, and a gas with an oxygen content of 80% is passed through it. After a heat treatment at 600° C. for 150 minutes, lithium iron phosphate red powder is obtained.
[0051] S3: An ICP test is performed on the lithium iron phosphate red powder obtained in step S2, and the molar ratio of Li, Fe and P is 0.837:1.002:1.005.
[0052] The planetary ball mill was used for dry grinding. Lithium iron phosphate red powder and lithium carbonate were added to the ball mill to make the molar ratio of Li, Fe and P in the lithium iron phosphate oxide mixture 1.048:1.002:1.002. The ball milling speed was 800rpm. After 10 hours, the lithium iron phosphate oxide mixture was obtained. Laser particle size test showed that the lithium iron phosphate oxide mixture had D10=0.69um, D50=1.92um and D90=5.42um.
[0053] S4: placing the ground lithium-supplemented oxidized lithium iron phosphate mixture in an inert atmosphere furnace, and simultaneously introducing a nitrogen gas flow through an inlet pipe 2 into a nitrogen gas-carrying small molecular organic carbonization container 1 outside the inert atmosphere furnace (see Figure 1), the container 1 is filled with ethanol solution (organic solution 4), and nitrogen is allowed to enter the bottom of the inner cavity of the container 1 from the inlet pipe 2. After contacting with the ethanol solution, the nitrogen gas flow with ethanol is used as a protective atmosphere to enter the inert atmosphere furnace from the outlet pipe 3. The ethanol content in the mixed gas is about 0.1% of the nitrogen gas flow. The temperature in the furnace is raised to 700°C and kept warm for 8 hours, so that the lithium iron phosphate mixed material of lithium supplementation oxidation is reduced in the reducing atmosphere and forms a carbon deposition coating. After natural cooling, the regenerated lithium iron phosphate positive electrode material is obtained.
[0054] The above-mentioned regenerated lithium iron phosphate positive electrode material was made into a 2035 button-type lithium battery, and charge and discharge tests were carried out in the cut-off voltage range of 2.0 to 3.75V. The first reversible capacity and the capacity retention rate after 1000T cycles were recorded. The results showed that the reversible capacity was 156.8mAh / g and the cycle performance was 92.9%, which fully met the requirements of commercial lithium iron phosphate batteries.
[0055] Comparative Example 2:
[0056] S1 is the same as step S1 of Example 2.
[0057] S2: The positive electrode black powder obtained in step S1 is transferred to a tube furnace, and after heat treatment at 600° C. for 150 min, lithium iron phosphate red powder is obtained.
[0058] S3 is the same as step S3 of Example 2.
[0059] S4 places the ground oxidized lithium iron phosphate mixture in a nitrogen furnace, raises the temperature in the furnace to 700° C., keeps the temperature for 8 hours, and obtains a regenerated lithium iron phosphate positive electrode material after natural cooling.
[0060] The lithium iron phosphate positive electrode material obtained in this comparative example 2 was made into a 2035 button battery, and a charge and discharge test was carried out in the cut-off voltage range of 2.0 to 3.75 V. The first reversible capacity and the capacity retention rate after 1000T cycles were recorded. The results were: the reversible capacity was 132.5 mAh / g, and the cycle performance was 27.6%.
[0061] Compared with Example 2, in the heat treatment of step S2 of Comparative Example 2, there is no oxygen-containing environment. Although a lithium source is added during grinding in step S3, nitrogen with carbonizable small molecule organic matter is not used as a protective atmosphere in step S4. The results show that the reversible capacity of Comparative Example 2 is much lower than that of Example 2, and the cycle performance is much lower than that of Example 2.
[0062] Embodiment 3:
[0063] S1 soaks the waste lithium iron phosphate battery in a 10% NaCl solution for 240 minutes, performs discharge treatment, and then disassembles and separates the positive electrode sheet; then places the obtained positive electrode sheet in N 2The waste lithium iron phosphate positive electrode black powder was obtained by sintering at 550°C in an atmosphere furnace for 60 minutes to separate the positive electrode sheet from the current collector.
[0064] S2: The positive electrode black powder obtained in step S1 is transferred to an oxygen-containing atmosphere furnace, and a gas with an oxygen content of 70% is passed through it. After a heat treatment at 700° C. for 240 minutes, lithium iron phosphate red powder is obtained.
[0065] S3: An ICP test is performed on the lithium iron phosphate red powder obtained in step S2, and the molar ratio of Li, Fe and P is 0.730:0.998:1.004.
[0066] The planetary ball mill was used for dry grinding. Lithium iron phosphate red powder and lithium acetate were added to the ball mill to make the molar ratio of Li, Fe and P in the lithium iron phosphate oxide mixture to be 1.053:1.001:1.005. The ball milling speed was 1000rpm. After 15 hours, the lithium iron phosphate oxide mixture was obtained. Laser particle size test showed that the lithium iron phosphate oxide mixture had D10=0.89um, D50=1.58um and D90=4.77um.
[0067] S4: placing the ground lithium-supplemented oxidized lithium iron phosphate mixture in an inert atmosphere furnace, and simultaneously introducing a nitrogen gas flow through an inlet pipe 2 into a nitrogen gas-carrying small molecular organic carbonization container 1 outside the inert atmosphere furnace (see Figure 1 ), container 1 is filled with acetone solution (organic solution 4), nitrogen is allowed to enter the bottom of the inner cavity of container 1 from the inlet pipe 2, and after contacting with the acetone solution, the nitrogen gas flow with acetone enters the inert atmosphere furnace from the outlet pipe 3 as a protective atmosphere. The acetone content in the mixed gas is about 0.3% of the nitrogen gas flow. The temperature in the furnace is raised to 700°C and kept for 15 hours, so that the lithium iron phosphate mixed material of lithium supplementation oxidation is reduced in the reducing atmosphere and forms a carbon deposition coating. After natural cooling, the regenerated lithium iron phosphate positive electrode material is obtained.
[0068] The above-mentioned regenerated lithium iron phosphate positive electrode material was made into a 2035 button-type lithium battery, and charge and discharge tests were carried out in the cut-off voltage range of 2.0 to 3.75V. The first reversible capacity and the capacity retention rate after 1000T cycles were recorded. The results showed that the reversible capacity was 155.6mAh / g and the cycle performance was 91.8%, which fully met the requirements of commercial lithium iron phosphate batteries.
[0069] Comparative Example 3:
[0070] Steps S1 and S2 are the same as those in Example 3.
[0071] S3: The lithium iron phosphate red powder obtained in step S2 is subjected to ICP testing, wherein the molar ratio of Li, Fe and P is 0.951:1.004:1.002.
[0072] The oxidized lithium iron phosphate mixture was obtained by dry grinding using a planetary ball mill at a ball milling speed of 1000 rpm for 15 hours. Laser particle size test showed that the oxidized lithium iron phosphate mixture had a D10 of 0.89 um, a D50 of 1.58 um, and a D90 of 4.77 um.
[0073] S4 places the ground oxidized lithium iron phosphate mixture in an inert atmosphere furnace, raises the temperature in the furnace to 600° C., keeps the temperature for 18 hours, and obtains a regenerated lithium iron phosphate positive electrode material after natural cooling.
[0074] The lithium iron phosphate positive electrode material obtained in this comparative example 3 was made into a 2035 button-type lithium battery, and a charge and discharge test was carried out in the cut-off voltage range of 2.0 to 3.75 V. The first reversible capacity and the capacity retention rate after 1000T cycles were recorded. The results were: the reversible capacity was 114.9 mAh / g, and the cycle performance was 14.5%.
[0075] Compared with Example 3, although the heat treatment in step S2 of Comparative Example 3 is carried out in an atmosphere with an oxygen content of 70%, no lithium source is added during grinding in step S3, and nitrogen with carbonizable small molecule organic matter is not used as a protective atmosphere in step S4. The results show that the reversible capacity of Example 3 is much higher than that of Comparative Example 3, and the cycle performance is 6.3 times that of Comparative Example 3.
[0076] Embodiment 4:
[0077] S1 soaks the waste lithium iron phosphate battery in a 10% NaCl solution for 90 minutes, performs discharge treatment, and then disassembles and separates the positive electrode sheet; then places the obtained positive electrode sheet in N 2 The waste lithium iron phosphate positive electrode black powder was obtained by sintering at 600°C in an atmosphere furnace for 60 minutes to separate the positive electrode sheet from the current collector.
[0078] S2: The positive electrode black powder obtained in step S1 is transferred to an oxygen-containing atmosphere furnace, and a gas with an oxygen content of 90% is passed through it. After a heat treatment at 400° C. for 240 minutes, lithium iron phosphate red powder is obtained.
[0079] S3: An ICP test is performed on the lithium iron phosphate red powder obtained in step S2, and the molar ratio of Li, Fe and P is 0.967:1.002:1.007.
[0080] The planetary ball mill was used for dry grinding. Lithium iron phosphate red powder and lithium oxalate were added to the ball mill to make the molar ratio of Li, Fe and P in the lithium iron phosphate supplemented oxidized lithium iron phosphate mixture 1.056:1.002:1.005. The ball milling speed was 400rpm. After 15 hours, the lithium iron phosphate supplemented oxidized lithium iron phosphate mixture was obtained. Laser particle size test showed that the lithium iron phosphate supplemented oxidized lithium iron phosphate mixture had D10=0.38um, D50=1.42um and D90=3.72um.
[0081] S4: placing the ground lithium-supplemented oxidized lithium iron phosphate mixture in an inert atmosphere furnace, and simultaneously introducing a nitrogen gas flow through an inlet pipe 2 into a nitrogen gas-carrying small molecular organic carbonization container 1 outside the inert atmosphere furnace (see Figure 1 ), the container 1 is filled with acetic acid solution (organic solution 4), and nitrogen is allowed to enter the bottom of the inner cavity of the container 1 from the air inlet pipe 2. After contacting with the acetic acid solution, the nitrogen gas flow carrying acetic acid enters the inert atmosphere furnace from the air outlet pipe 3 as a protective atmosphere. The acetic acid content in the mixed gas is about 0.1% of the nitrogen gas flow. The temperature in the furnace is raised to 800°C and kept warm for 8 hours, so that the lithium iron phosphate mixed material supplemented with lithium oxide is reduced in the reducing atmosphere and forms a carbon deposition coating. After natural cooling, the regenerated lithium iron phosphate positive electrode material is obtained.
[0082] The above-mentioned regenerated lithium iron phosphate positive electrode material was made into a 2035 button-type lithium battery, and charge and discharge tests were carried out in the cut-off voltage range of 2.0 to 3.75V. The first reversible capacity and the capacity retention rate after 1000T cycles were recorded. The results showed that the reversible capacity was 156.5mAh / g and the cycle performance was 93.8%, which fully met the requirements of commercial lithium iron phosphate batteries.
[0083] Comparative Example 4:
[0084] Step S1 is the same as that in Example 4.
[0085] S2: The positive electrode black powder obtained in step S1 is transferred to a tube furnace, and after heat treatment at 40°C for 240 minutes, lithium iron phosphate red powder is obtained.
[0086] S3: The lithium iron phosphate red powder obtained in step S2 is subjected to ICP testing, wherein the molar ratio of Li, Fe and P is 0.967:1.002:1.007.
[0087] The oxidized lithium iron phosphate mixture was obtained by dry grinding using a planetary ball mill at a ball milling speed of 400 rpm for 15 hours. Laser particle size test showed that the oxidized lithium iron phosphate mixture had D10 = 0.38 um, D50 = 1.42 um, and D90 = 3.72 um.
[0088] S4 places the ground oxidized lithium iron phosphate mixture in a nitrogen furnace. The nitrogen in the furnace does not carry any organic matter. The temperature in the furnace is raised to 800°C and kept warm for 8 hours. After natural cooling, a regenerated lithium iron phosphate positive electrode material is obtained.
[0089] The lithium iron phosphate positive electrode material obtained in this comparative example 4 was made into a 2035 button battery, and a charge and discharge test was carried out in the cut-off voltage range of 2.0 to 3.75 V. The first reversible capacity and the capacity retention rate after 1000T cycles were recorded. The results were: the reversible capacity was 95.5 mAh / g, and the cycle performance was 4.1%.
[0090] By comparison, it can be seen that in step S2 of comparative example 4, there is no oxygen-containing environment, and no lithium source is added in step S3; step S4 does not use an inert gas containing carbonizable small molecular organic matter. The results show that the reversible capacity of comparative example 4 is much lower than that of example 4, and the cycle performance is only 1 / 20 of that of example 4.
[0091] The above-mentioned embodiments of the present invention are only part of the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made by those skilled in the art without departing from the essence of the present invention are within the protection scope of the present invention.
Claims
1. A method for repairing and regenerating waste lithium iron phosphate positive electrode materials, characterized in that: The steps include: S1. Discharging and dismantling the waste lithium iron phosphate battery to separate the lithium iron phosphate positive electrode sheet, and then heat-treating the obtained positive electrode sheet under an inert atmosphere to separate the lithium iron phosphate positive electrode sheet from the current collector to obtain the waste lithium iron phosphate positive electrode black powder; S2 The waste lithium iron phosphate positive electrode black powder is heat-treated again in an environment furnace with an oxygen content higher than 60%, the heat treatment temperature is 400℃~800℃, the time is 60~300min, and the surface of the lithium iron phosphate red powder is oxidized while removing impurities to obtain oxidized lithium iron phosphate red powder; S3: testing the P, Fe, and Li content of the lithium iron phosphate oxide red powder obtained in step S2, and appropriately supplementing the lithium source according to the test result, and then mixing the lithium iron phosphate oxide red powder with the lithium source by ball milling to obtain a lithium-supplemented lithium iron phosphate oxide mixture; S4 placing the lithium-replenished oxidized lithium iron phosphate mixture in a reducing atmosphere furnace, passing an inert gas carrying carbonizable small molecular organic matter, and after heat treatment, allowing the lithium-replenished oxidized lithium iron phosphate mixture to be carbon-deposited and reduced in the reducing atmosphere to obtain a regenerated lithium iron phosphate positive electrode material; The carbonizable small molecule organic matter is at least one of methanol, ethanol, acetone, formic acid, acetic acid, ethyl acetate or ether. The inert gas carrying the carbonizable small molecule organic matter is heat treated in a reducing atmosphere furnace at a temperature of 600-900° C. for a holding time of 6-18 hours.
2. A method for repairing and regenerating waste lithium iron phosphate positive electrode materials as claimed in claim 1, characterized in that: In the step S1, the discharge treatment is to soak the waste lithium iron phosphate battery in a 5wt% to 20wt% NaCl solution for 30 to 240 minutes, so that all the active lithium ions inside the waste lithium iron phosphate battery are embedded back into the lithium iron phosphate positive electrode material while discharging.
3. A method for repairing and regenerating waste lithium iron phosphate positive electrode materials as claimed in claim 1, characterized in that: In the step S1, the inert atmosphere is one or more of nitrogen, argon, and helium, the heat treatment temperature is 300 to 600° C., and the heat treatment time is 30 to 180 min.
4. A method for repairing and regenerating waste lithium iron phosphate positive electrode materials as claimed in claim 1, characterized in that: In the step S3, the lithium source is supplemented so that the molar ratio of P, Fe and Li elements in the lithium iron phosphate red powder satisfies the following relationship: P:Fe:Li=(1±0.01):(1±0.01):(1.05±0.005).
5. A method for repairing and regenerating waste lithium iron phosphate positive electrode materials as claimed in claim 1 or 4, characterized in that: In the step S3, the lithium iron phosphate red powder and the lithium source are mixed and ball-milled at 400-1200 rpm for 6-15 hours, and the particle size after mixing satisfies: D50≤2um, (D90-D10) / D50≤2.
5.
6. A method for repairing and regenerating waste lithium iron phosphate positive electrode materials as claimed in claim 1 or 4, characterized in that: In the step S3, the lithium source is at least one of lithium carbonate, lithium acetate, lithium hydroxide, lithium nitrate, lithium oxide, lithium phosphate, lithium chloride or lithium fluoride.
7. A method for repairing and regenerating waste lithium iron phosphate positive electrode materials as claimed in claim 1, characterized in that: In the step S4, the preparation method of the inert gas entrained with carbonizable small molecule organic matter is as follows: liquid carbonizable small molecule organic matter is placed in a container, an air inlet pipe and an air outlet pipe are arranged on the container, wherein the air inlet pipe is a long conduit, one end of which is fed with inert gas, and the other end is inserted into the container, the pipe mouth of the air inlet pipe is close to the bottom of the container, so that the inert gas and the carbonizable small molecule organic matter are fully mixed to form bubbles entrained with carbonizable small molecule organic matter and overflow; one end of the air outlet pipe is connected to the inner cavity of the container, and the other end is connected to the reducing atmosphere furnace, and the inert gas entrained with carbonizable small molecule organic matter rises and enters the reducing atmosphere furnace through the air outlet pipe.
8. A lithium iron phosphate battery prepared by the method for repairing and regenerating waste lithium iron phosphate positive electrode materials as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Selective oxidation-reduction regeneration method of waste lithium iron phosphate, regenerated lithium iron phosphate and lithium ion battery
CN113036253A
Direct regeneration method of waste lithium iron phosphate positive electrode material
CN114744315A